Hatred and Profits: Under the Hood of the Ku Klux Klan* - Fryer, Roland G.; Levitt, Steven D. (Quarterly Journal of Economics, 2012)
In this article, we analyze the 1920s Ku Klux Klan, those who joined it, and its social and political impact by combining a wide range of archival data sources with data from the 1920 and 1930 U.S censuses. We find that individuals who joined the Klan in some cities were more educated and more likely to hold professional jobs than the typical American. Surprisingly, we find little evidence that the Klan had an effect on black or foreign-born residential mobility or vote totals. Rather than a terrorist organization, the 1920s Klan is best described as social organization with a very successful multilevel marketing structure fueled by an army of highly incentivized sales agents selling hatred, religious intolerance, and fraternity in a time and place where there was tremendous demand.